Ð¥Ð°Ñ€Ð°ÐºÑ‚ÐµÑ€ Ð¸Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ñ ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ð½Ð¾-Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ñ… Ñ…Ð°Ñ€Ð°ÐºÑ‚ÐµÑ€Ð¸ÑÑ‚Ð¸Ðº ÐºÐ»ÐµÑ‚Ð¾Ðº Ñ„ÐµÑ‚Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ð¿Ð¾ÑÐ»Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð² Ð·Ð°Ð²Ð¸ÑÐ¸Ð¼Ð¾ÑÑ‚Ð¸ Ð¾Ñ‚ Ð¸Ñ… ÑÑ€Ð¾ÐºÐ¾Ð² Ð³ÐµÑÑ‚Ð°Ñ†Ð¸Ð¸ - Ostankov, M. V.; Bondarovich, N. A.; Rassokha, I. V.; Goltsev, A. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The efficiencies of three freezing programs (two, three- and four-stage) basing on the estimation of morphofunctional state and therapeutic potential of cryopreserved fetal liver cells (СFLCs) of 15 and 19 gestation days were studied. The investigations have shown that during freezing of FLC-15 the most effective was two-stage cryopreservation regimen under 10% DMSO protection, which provided higher content of survived and hemopoietic stem cells (CD34+CD38–). From this point of view the most suitable for cFLC-19 was the use of 12.5% DMSO at three-stage freezing program. In C3H mice genetically determined to the development of breast cancer the most manifested reduction of the frequency of tumor development and higher survival were observed after application of cFLC-15.